Development and Research of an Autonomous Device for Sending a Distress Signal Based on a Low-Orbit Satellite Communication System - Ondyrbayev, Nurbolat; Zhumagali, Sabyrzhan; Chezhimbayeva, Katipa; Zhumanov, Yelaman; Nurzhauov, Nursultan (Journal of Applied Data Sciences, 2024)
Due to the importance of providing reliable communication for sending distress signals, research on the development of an autonomous device via low-orbit satellites is becoming particularly relevant, offering innovative solutions capable of providing fast and reliable communication in extreme situations. The purpose of this study was to investigate a device capable of operating autonomously in emergency situations and providing fast transmission of a signal about the need for help. The comparative method, statistical method, and analysis were used in the framework of research. The results of the study showed the significant potential of Long-Range Wide Area Networks (LoRaWAN) technology in the field of wireless communication. It provides high stability and noise immunity of data transmission, which makes it an attractive choice for various applications. Due to its high scalability, LoRaWAN is capable of servicing tens and hundreds of thousands of devices, making it an ideal solution for large-scale projects. LoRaWAN can achieve data transmission rates between 0.3 kbps to 50 kbps, with power consumption as low as 1.2 µA in sleep mode and 28 mA in transmit mode, and communication ranges up to 15 km in rural environments. Because of its low power consumption, it is ideal for use in battery-powered devices such as smart and distress sensors. In addition, it was found that the use of EBYTE E32 modules in LoRaWAN devices ensures reliable and efficient data transfer. The study confirms the potential of LoRaWAN technology for developing efficient and reliable wireless communication systems for various Internet of Things applications, ensuring reliable data transmission under various conditions. The results obtained are of great practical importance for the creation and further improvement of autonomous devices for the rapid sending of distress signals, contributing to increased safety and responsiveness to emergency situations.